Vascular airway compression management in a case of aortic arch and descending thoracic aortic aneurysm - Alok Kumar (Annals of Cardiac Anaesthesia, 2016)
Airway compression due to distal aortic arch and descending aortic aneurysm repair has been documented. This case of tracheal and left main stem bronchus compression due to aortic aneurysm occurred in a 42-year-old man. The airway compression poses a challenge for the anesthesiologist in airway management during aortic aneurysm repair surgery. The fiber-optic bronchoscope is very helpful in decision-making both preoperatively and postoperatively in such cases. We report a case of airway compression in a 42-year-old patient who underwent elective distal aortic arch and descending aortic aneurysm repair.